Analisis Efisiensi Anggaran Pangan Pemerintah Provinsi DKI Jakarta dalam Meningkatkan Ketersediaan dan Aksesibilitas Pangan - Sarah Nurlaily; Faza Ainur Rahma; Eva Hany Fanida; Revienda Anita Fitrie (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Food security is a strategic issue in regional development, particularly in urban areas with limited food production resources. Jakarta, as the center of government and national economy, is highly dependent on food supplies from other regions, making food budget management crucial for maintaining food availability and accessibility. This study aims to analyze the efficiency of the food budget managed by the Jakarta Provincial Government and its implications for improving food availability and accessibility. The method used is a literature study (library research) with a qualitative, descriptive, and analytical approach, utilizing secondary data from scientific journals, books, research reports, and government policy documents. The results indicate that efficient food budget management plays a crucial role in supporting food availability stability and increasing public access to adequate and affordable food. Effective, transparent, and performance-based budget management can enhance the effectiveness of food security programs and strengthen the food distribution system in urban areas. Therefore, local governments need to ensure that food budget allocations are used appropriately to achieve optimal impact on improving community food security.